Peran Liturgi Sebagai Benteng Rohani Gereja Melawan Godaan Judi Online di Kalangan Jemaat - Munthe, Eben (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
The temptation of online gambling has become a serious challenge amid the rapid advancement of technology. Various factors, such as social environmental influence, emotional needs, and spiritual dissatisfaction, make individuals vulnerable to this temptation. Online gambling offers the illusion of instant gains but often leads to moral, emotional, and financial destruction. In this context, church liturgy plays a strategic role as a spiritual fortress to resist this temptation. Liturgy elements such as confession of sin, prayer, worship, and sermons not only strengthen the faith of the congregation but also build awareness of the dangers of online gambling. Relevant and contextual liturgy, including the use of digital technology, enables the church to reach its congregation effectively. Through this approach, the church helps its members maintain spiritual integrity, build supportive communities, and guide them to live in gratitude and simplicity according to God’s will. This strategy is a crucial solution to facing moral threats in the modern era.